ANALISA DESAIN BETON PRATEGANG TIPE I-GIRDER PADA JEMBATAN SAMOTA - Hidayati, Nurul; Hariyadi, Hariyadi; Sahlinda, Ranni (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
Samota Bridge is a bridge crossing the Brang Biji River in Sumbawa Regency, West Nusa Tenggara. Samota Bridge will be redesigned using prestressed concrete with a type of PC I Girder with a span of 80 m and a width of 11 m. The bridge analysis standards used are loading standards for bridges (SNI 1725: 2016) and bridge planning standards against earthquake loads (SNI 2833: 2016). The loading analyzed is the analysis of own load, dead load, additional dead load, temperature influence, shrinkage and creep influence, brake force, earthquake load, wind load, prestress loss analysis, deflection and moment. Then, the reinforcement calculation is carried out on the PC I-Girder to the bridge elastomer planning. The results of the redesigned of the Samota Bridge with a span of 80 m (40+40) obtained the optimum height of the PC I-Girder needed is 2.10 m consisting of 4 tendons 2 on the left and 2 on the right with 12 strands in each tendon. The strands diameter is 15.24 mm and the duct diameter is 85 mm. The dead load (MS) received by PC- I Girder is 636,777.60 kg.m, the additional dead load (MA) received is 59,153.04 kg.m, 406,980 kg.m for "D" lane load, 8,183.25 kg.m for brake force, 3,003.25 kg.m for wind load and 179,378.73 kg.m for earthquake load. The total prestress loss due to anchor friction, friction in the cable, due to creep and shrinkage, relaxation and elastic shortening of concrete was 2,965.79 kN with a prestress loss percentage of 29.63%.